Nominal Income Targeting as an Alternative Monetary Policy Regime : A DSGE Model Analysis - Peichl, Jan; Maršál, Aleš; Potužák, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
This thesis explores Nominal Income Targeting (NIT) as an alternative monetary policy regime within the Dynamic Stochastic General Equilibrium (DSGE) model framework in comparison with Taylor rule. The study begins with a comprehensive review of the theoretical foundations of NIT, examining its historical development, economic rationale, and the implications for economic dynamics. This foundation is then applied in a DSGE model, calibrated to represent a small open economy similar to the Czech Republic, to assess the practical effectiveness of NIT under various economic scenarios. The analysis reveals that the nominal income-growth target results in lower welfare loss compared to both the Taylor rule and the nominal income-level target, particularly in response to different types of shocks, namely price level, exchange rate, and total factor productivity (TFP) shocks. The nominal income-growth target effectively stabilizes consumption and output, offering robust performance across scenarios, while the Taylor rule and nominal income-level target show larger declines in key macroeconomic variables. The study’s findings are consistent with existing literature mentioned in the thesis. However, the analysis also identifies limitations in the implementation of the nominal income-level target, suggesting that the specific rule used may not fully capture the complexities of this regime. Overall, this thesis contributes to the debate on the improvement of monetary policy by providing compilation of existing literature as well as an evaluation of NIT within a DSGE framework. The results indicate that NIT in the form of a nominal income-growth target could possibly be an effective tool for central banks in maintaining economic stability and growth.
Vedoucí práce: Aleš Maršál
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: ekonomie [obor dipl. práce]; diplomové práce; master's theses